TO STUDY THE EFFECTS OF DIFFERENT TIMING OF DELAYED CORD CLAMPING ALONG WITH MILKING ON HAEMATOLOGICAL PARAMETERS IN NEWBORNS - A RANDOMIZED CONTROL TRIAL - PILANIA, PRATIBHA; MAHALA, URMILA; PRAKASH, OM (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Evaluation of the hematological parameter in newborn by delayed cord clamping at 60 s and at 180 s. Comparison of the improvement in hematological parameters, that is, hemoglobin and serum ferritin in newborn by both methods. Methods: This was randomized, controlled, and comparative study conducted during April 2021 to February 2022 at the Department of Obstetrics and Gynaecology, SMS Medical College, Jaipur. The study included sample size of 60 cases (30 cases in each group). 60 cases were randomly allocated to either 60 s (Group A) or 180 s (Group B) groups of delayed cord clamping. The study included all singleton pregnant women >34 weeks of gestational age. Results: Mean hemoglobin±standard deviation of neonate at birth for Group A was13.53±0.56 g/dL and for Group B it was 13.85±0.55 g/dL. Mean hemoglobin ± standard deviation at 6 month for Group A was 13.19±0.53 g/dL and for Group B was 13.53±0.55 g/dL. Mean serum ferritin±standard deviation of infant at for Group A was 12.46±0.45% and for Group B was 12.86±0.55%. Conclusion: Neonatal hemoglobin and serum ferritin were significantly higher in180 s delayed cord clamping as compared to 60 s delayed cord clamping group.